2013
DOI: 10.1186/1477-7819-11-272
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery pseudoaneurysm after a left upper sleeve lobectomy

Abstract: A 55-year-old man was re-admitted for persistent hemoptysis and high fever three weeks after an initial left upper sleeve lobectomy for a central squamous lung cancer tumor. Pulmonary artery pseudoaneurysm and pulmonary infection were confirmed by multidetector computed tomography angiography and subsequent emergency completion pneumonectomy. The development of pulmonary artery pseudoaneurysm, secondary to post-operative pulmonary infection and pulmonary vascular manipulation, is rare and prompt surgical manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Because of higher tendency of getting ruptured, on rare occasions these present with hemorrhages and other catastrophic events like intrapulmonary hemorrhage, hemothorax, or intrabronchiolar hemorrhage. Idiopathic pulmonary artery pseudoaneurysm is more commonly found in elderly females, besides that no other demographic event has been attributed to pseudoaneurysm formation in pulmonary vasculature 7 . Pulmonary artery pseudoaneurysm are seen either after traumatic event, tuberculosis, pneumonia, vasculitis (few common ones: Behcet's syndrome and Hughes–Stovin syndrome which is characterized by recurrent thrombophlebitis and pulmonary artery aneurysm) or congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of higher tendency of getting ruptured, on rare occasions these present with hemorrhages and other catastrophic events like intrapulmonary hemorrhage, hemothorax, or intrabronchiolar hemorrhage. Idiopathic pulmonary artery pseudoaneurysm is more commonly found in elderly females, besides that no other demographic event has been attributed to pseudoaneurysm formation in pulmonary vasculature 7 . Pulmonary artery pseudoaneurysm are seen either after traumatic event, tuberculosis, pneumonia, vasculitis (few common ones: Behcet's syndrome and Hughes–Stovin syndrome which is characterized by recurrent thrombophlebitis and pulmonary artery aneurysm) or congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…There are a handful of cases with invasive cancer presenting with pseudoaneurysm of pulmonary vasculature which resolve after the treatment of cancer with systemic chemotherapy 1 , 2 , 4 , 5 . Few case reports mention the occurrence of pseudoaneurysm of pulmonary vasculature after local invasive procedures like placement of Swan–Ganz catheter or after sessions of local chemotherapy 3 , 7 , 8 . Few cases mention adriamycin as the most commonly associated chemotherapy agent with pseudoaneurysm especially in patients undergoing transarterial chemoemobilzation (TACE) for hepatocellular carcinoma 6 8 , 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bao et al have reported a PAP following left upper sleeve lobectomy for a central squamous cell lung cancer. 2 The PAP was attributed to both inflammation and iatrogenic PA trauma during lobectomy. Therefore, an operative procedure can be a contributing cause of PAP.…”
Section: Discussionmentioning
confidence: 99%